2015
DOI: 10.1108/jeim-01-2015-0001
|View full text |Cite
|
Sign up to set email alerts
|

Technological, organisational and environmental factors influencing managers’ decision to adopt cloud computing in the UK

Abstract: Purpose – The purpose of this paper is to determine the factors influencing managers’ decision to adopt cloud computing in the UK using the “Technology-Organisation-Environment” (TOE) framework. Design/methodology/approach – Data were collected through a self-created questionnaire based survey that was completed by 257 mid-to-senior level decision-making business and information technology (IT) professionals from a range of UK end-user o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
282
4
25

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 270 publications
(327 citation statements)
references
References 34 publications
16
282
4
25
Order By: Relevance
“…Bhat [36] suggested "laws and regulation" as the institutional factors. Besides, Yeboah-Boateng and Essandoh [37] mentioned the relative important influence of "adequate users and technical support" as the environmental factors. Oliveira et al [11] created a model to assess the determinants which influence to adopt cloud computing, and presented the holistic assessment factors by the model.…”
Section: Cloud Computing Adoption and Influence Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bhat [36] suggested "laws and regulation" as the institutional factors. Besides, Yeboah-Boateng and Essandoh [37] mentioned the relative important influence of "adequate users and technical support" as the environmental factors. Oliveira et al [11] created a model to assess the determinants which influence to adopt cloud computing, and presented the holistic assessment factors by the model.…”
Section: Cloud Computing Adoption and Influence Factorsmentioning
confidence: 99%
“…They proposed a toolkit that decision-makers can use to identify their risks and coordinate suitable tools and techniques [35]. A recent study of cloud adoption was conducted in terms of a national perspective and small and medium enterprises [33,36,37], and the case studies described the direct influences of cloud computing on the organization in a wide range of activities, including global enterprises [38,39].…”
Section: Cloud Computing Adoption and Influence Factorsmentioning
confidence: 99%
“…Taking in such support helps the organization to avoid any internal barriers and opposition to change. It can be concluded that top management support is vital for organizations searching to produce a competitive environment, whilst also providing the resources needed to adopt cloud service [61].…”
Section: ) Top Management Supportmentioning
confidence: 99%
“…The more the technology is recognized as being compatible with existing systems and organizational values and beliefs, the more likely organizations are to think about adopting cloud computing. Cloud computing allows organizations to keep up with new technology without affecting existing legacy systems aligned with their different organizational, managerial, and operational needs [61].…”
Section: ) Complexitymentioning
confidence: 99%
“…They found that relative advantage, technological readiness, top management support, and size had positive effects on CC adoption, while complexity has a negative effect. Another similar study has been conducted in [9], which examines the effects of a set of technological factors concerning the CC technology (relative advantage, complexity and compatibility), organizational factors (top management support, size, technological readiness) and environmental factors (competitive pressure, trading partners pressure) on CC adoption, using data collected from 257 mid-to-senior level decision-making business and ICT professionals from UK enterprises. They concluded that competitive pressure, complexity, technology readiness and trading partner pressure have a significant influence on the adoption of CC services.…”
Section: Introductionmentioning
confidence: 99%